Symposium 6: Participatory Design for Awareness Features: Enhancing Interaction in Communities of Practice - El Helou, Sandy; Tzagarakis, Manolis; Gillet, Denis; Karacapilidis, Nikos; Yu, Chiu Man (Proceedings of the International Conference on Networked Learning, 2008)
In the framework of the European Integrated Project PALETTE, the École Polytechnique Fédérale de Lausanne (EPFL) and the University of Patras are developing mediation services. These services aim at sustaining collaboration, supporting tacit and explicit knowledge management and enhancing individual and organizational learning in communities of practice (CoPs). Defined by Dourish and Belloti as "an understanding of the activities of others, which provides a context for one’s own activity", awareness is one of the most crucial needs expressed by communities of practice in the framework of the participatory design process implemented within the Palette project. Awareness of past and current actions in shared environments and over shared artifacts motivates participation and guides the members’ decisions and course of actions. This paper describes the approach adopted by two Web-based collaboration support applications, namely eLogbook and CoPe_it!, for developing awareness services. CoPs needs, in terms of awareness, were identified through the participatory design approach. Then, a combination of relevant awareness types found in the literature was adopted in order to address the identified awareness requirements. The resulting awareness services implemented by Palette’s mediation services (eLogbook and CoPe_it!) are presented. In particular, the kind of awareness information provided and its rendering means are described. For each tool, the available awareness functionality is related to the awareness type it contributes.